Internet banking: Analysing encouragement and impediment factors among academicians - Jano, Zanariah; Janor, Hawati; Elangsegaran, Rajendraan; Khamis, Noorli; Md Saad, Mohd Shamsuri (IRACST, 2012)
The paper aims to explore the encouragement and impediment factors for consumers to adopt internet banking services. The study should provide effective strategies for banking institutions on how to maximise the rate of adoption. A survey involving a sample size of 200 was conducted by sending questionnaires to lecturers in 20 public universities in Malaysia. The Decomposed Theory of Planned Behaviour model (DTPB)was used. While "Perceived Usefulness" and "Features of websites" were the top factors which encourage the adoption of internet banking,"Culture" was the most significant impediment in adoption. In terms of moderating variables, only a few variables show significant impact on certain factors. Age and income impacted only on "External environment" whereas WAP feature had an impact only on "Perceived usefulness'. Other variables have not shown significant effect on the factors. The findings suggest that banking institutions should plan effective strategies to enhance the push factors and to counter the barrier of culture in order to enhance internet banking adoption. This study offers valuable strategies for marketers to rethink how to educate potential customers and promote internet banking using innovative approaches. Recommendations are offered to financial institutions to plan effective strategies to enhance adoption of internet banking. The potential factors influencing internet banking adoption also provide useful insights for other developing countries.